M. Valančius' views on primary education after the 1863 uprising - Karčiauskienė, M. (Psichologija, 1977)
The article deals with M. Valančius' views on the official tsarist schooling system, the change of his attitude towards it after the 1863 uprising. The article highlights Valančius' criticism of tsarst policy of education and schooling in Lithuania. There is a special reference to the book "Pasakojimai Antano Tretininko", because it touches on Valančius' attitude towards private (secret) education not approved by the State.
Keywords: Valančius; primary education; 1863 uprising